Skills Berbohong Generasi Bangsa - Nursanti, Nursanti; Prabawa, Sambas; Hendriawan, Erry (STKIP Pasundan, 2024)
This research aims to strengthen the competence of civic skills of students. Through learning civic education by shaping the mindset of students to be critical, understand and be able to carry out their rights and obligations to become smart, skilled and characterized citizens in the midst of the development of an increasingly broad era. The problems that will be discussed in this study are: (1) how the competence of civic skills in learning civic education at SMK Pasundan 1 Cimahi; (2) how the formation of moral intelligence of students at SMK Pasundan 1 Cimahi; (3) How much influence the competence of civic skills on the formation of moral intelligence of students in learning civic education at SMK Pasundan 1 Cimahi. The purpose of the study was to determine the effect of civic skills competence on the formation of students' moral intelligence in civic education learning at SMK Pasundan 1 Cimahi. The research method used in this research is descriptive quantitative method with sampling technique, namely Probability Sampling. The results of the study are (1) The value for the Civic Skills Competency variable (X) is 60.19 the classification is said that the Civic Skills Competency variable (X) is classified as a